2010
DOI: 10.1017/s1062798709990305
|View full text |Cite
|
Sign up to set email alerts
|

Academic Systems and Professional Conditions in Five European Countries

Abstract: Despite the tendency to create a European Higher Education and Research area, academic systems are still quite different across Europe. We selected five countries (Finland, Germany, Italy, Norway and the UK) to investigate how the differences have an impact on a number of aspects of the working conditions of academic staff. One crucial aspect is the growing diversification of professional activity: reduction of tenured and tenure tracked position, the growing number of fixed-term contracts for both teaching an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…As can be expected, these changes are not restricted to the Anglophone world and are played out in other jurisdictions. In their examination of academic working conditions in five European countries (Finland, Germany, Italy, Norway and the UK) using the CAP data, Cavalli and Moscati (2010) concluded that the growing diversification of professional activity has resulted in the reduction of tenured and tenure track positions, a growing number of fixedterm contracts for both teaching and research and a growing uncertainty amongst academics regarding long-term stability, all of which has resulted in decreased dissatisfaction amongst faculty members in the five nations.This emerging hierarchy amongst academic staff is compounded by long-term downward trends in academic salaries within some countries (Robinson, 2005). As Finkelstein contends, 'the notion of academics as a "cohesive group" united by a common pre-service socialisation experience will become increasingly limited in its application to a shrinking core' (Finkelstein, 2010, p. 153).…”
mentioning
confidence: 99%
“…As can be expected, these changes are not restricted to the Anglophone world and are played out in other jurisdictions. In their examination of academic working conditions in five European countries (Finland, Germany, Italy, Norway and the UK) using the CAP data, Cavalli and Moscati (2010) concluded that the growing diversification of professional activity has resulted in the reduction of tenured and tenure track positions, a growing number of fixedterm contracts for both teaching and research and a growing uncertainty amongst academics regarding long-term stability, all of which has resulted in decreased dissatisfaction amongst faculty members in the five nations.This emerging hierarchy amongst academic staff is compounded by long-term downward trends in academic salaries within some countries (Robinson, 2005). As Finkelstein contends, 'the notion of academics as a "cohesive group" united by a common pre-service socialisation experience will become increasingly limited in its application to a shrinking core' (Finkelstein, 2010, p. 153).…”
mentioning
confidence: 99%
“…It also arises from an increasing separation of teaching and research activity, and the targeting of income streams to specific activities (Whitchurch and Gordon 2013a, b;Courtois and O'Keefe 2015;Lama and Jouille 2015;Locke et al 2016). Such trends have also been identified in Canada, the USA, Australia, and Europe (Coates and Goedegebuure 2010;Cavalli and Moscati 2010;Jones et al 2012;Musselin 2013;Finkelstein et al 2016;Kezar and Maxey 2016;Kim 2017). Thus, in the USA, as is now the case in the UK, less than 50% of academic staff have contracts that formally include both teaching and research.…”
Section: Introductionmentioning
confidence: 86%
“…65-89 % of university scientists, depending upon country, have a prime interest in research rather than teaching (Abreu et al, 2009;Cavalli and Moscati, 2010). However, 'Teaching' is not optional (Sect.…”
Section: What Constrains Scientists' Working With Industry?mentioning
confidence: 99%
“…Academic systems vary by country (Cavalli and Moscati, 2010;Coates et al, 2009). However, in general, tenure with its guaranteed job security (Adams, 2006) has declined (e.g.…”
Section: Careermentioning
confidence: 99%